Restriction of Environmental Radioactive Background in Al- Qadisiya Governorate by Using Technical HPGe - Kawthar Hasan Obeis (Al-Qadisiyah Journal of Pure Science, 2017)
the present study, selected agricultural, and animal rearing areas in Al-Qadisiya governorate In the district of Shameya were chosen to conduct the work . 10 samples of each of plant(The grain) and milk were collected from the same places. Using high purity germanium detector (HPGe), After analysing the studied spectrums samples , It was Cs) is 137Th,232U , 238K, 40of plant samples of( found that the average radioactivity(337.004±30) Bq / kg, (7.26±0.43)Bq / kg , (7.15±0.42) Bq/kg, (2.39±0.24)Bq / kg respectively , The milk samples the results were (286.36±28)Bq/kg, (1.411±0.18)Bq/kg ,(1.607±0.2)Bq/kg , (1.39±0.18)Bq/kg respectively , The average equivalent radium was calculated of plant samples is (43.429)Bq/kg , The average equivalent radium was calculated of milk samples is (25.69)Bq/kg . The averages value of the absorbed dose in for 1 -nGy.h)13.54and (1 -were (21.843) nGy.h of plant samples) (nGy per hour)the air (the milk samples . The hazard index internal and external of plant samples was about (0.13) , (0.11)respectively , and (0.073) ,( 0.069)for the milk samples respectively . The effective dose equivalent (EDE), from taking milk, was determined, depending on . 226and Ra40 , K 137specific activity of Cs By comparing the results withsome prior studies , It was found that the levels of radiation for samples studied within the permissible limits globally .